Global stochastic trends in growth, interest and inflation. Is the post-Bretton-Woods era driven by the Volcker disinflation? - Reinhold Heinlein; Hans-Martin Krolzig (University of Kent, School of Economics, 2013)
This note aims to identify the stable long-run relationships as well as unstable driving forces of the world economy using an aggregated approach involving the four largest currency blocks. The small global macromodel encompasses aggregated quarterly US, UK, Japanese and Euro Area data for the post-Bretton-Woods era. Three stable long-run relationships are found: output growth, the global term spread and an inflation climate measure. The common stochastic trend of the global economy is found to be dominated by real short-term interest rate shocks, reflecting the strong increase of the global real rates during the Volcker disinflation period as a dominating event of the last 40 years of macro history.
Keywords: C32; C50; C82; 330; Cointegration; Real interest rates; Volcker disinflation; Multi-country model; Divisia index